2021
DOI: 10.1002/adfm.202106116
|View full text |Cite
|
Sign up to set email alerts
|

Modular Type III Porous Liquids Based on Porous Organic Cage Microparticles

Abstract: The dispersion of particulate porous solids in size-excluded liquids has emerged as a method to create Type III porous liquids, mostly using insoluble microporous materials such as metal-organic frameworks and zeolites. Here, the first examples of Type III porous liquids based on porous organic cages (POCs) are presented. By exploiting the solution processability of the POCs, racemic and quasiracemic cage microparticles are formed by chiral recognition. Dispersion of these porous microparticles in a range of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 39 publications
5
50
1
Order By: Relevance
“…To date, a wide variety of liquids have been used, including organic solvents, oils, and ionic liquids. 37,38 For this study, we screened a small number of liquids that have previously been reported as being size-excluded for POCs and MOFs, including silicone oil AR 20, and the ionic liquids ). Ionic liquids are good candidates for porous liquids due to their low vapour pressures, compatibility with organic and inorganic materials,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a wide variety of liquids have been used, including organic solvents, oils, and ionic liquids. 37,38 For this study, we screened a small number of liquids that have previously been reported as being size-excluded for POCs and MOFs, including silicone oil AR 20, and the ionic liquids ). Ionic liquids are good candidates for porous liquids due to their low vapour pressures, compatibility with organic and inorganic materials,…”
Section: Resultsmentioning
confidence: 99%
“…As for porous solids, the most common gas release mechanisms are pressure and temperature swings. 11,29,30 This significantly limits the solvent choice in a porous liquid, restricting us to solvents that have a low or (ideally) near-zero vapour pressure. 11,31 There is also a significant parasitic energy penalty with pressure and temperature swings.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide variety of liquids have been used, including organic solvents, oils, and ionic liquids. 37,38 For this study, we screened a small number of liquids that have previously been reported as being size-excluded for POCs and MOFs, including silicone oil AR 20, and the ionic liquids ). Ionic liquids are good candidates for porous liquids due to their low vapour pressures, compatibility with organic and inorganic materials, and their ability to be tailored to suit different applications.…”
Section: Resultsmentioning
confidence: 99%
“… 49 While most of these systems relied on the use of a MOF, ZIF, or zeolite, as the porous material, more recently there have been examples of alternative pore carriers being used to form type III porous liquids, including the dispersion of HS nanospheres in dimethylaminoethoxyethanol, 50 hollow carbon nanospheres in polymeric ionic liquids, 51 and POC microparticles in a range of oils and ionic liquids. 52 …”
Section: Key Milestones In the Development Of Porous Liquidsmentioning
confidence: 99%